2011
DOI: 10.1007/s10682-011-9515-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and geographic structure of an insect resistant and a susceptible type of Barbarea vulgaris in western Europe

Abstract: Interactions between herbivores and plants are believed to have been important drivers of biodiversity. However, to drive an initial resistance divergence into different evolutionary lineages and taxa, these interactions have probably been embedded in other processes of divergence, like allopatric isolation. The cruciferous plant Barbarea vulgaris ssp. arcuata occurs in Denmark in two types: one (G) is resistant to most genotypes of the flea beetle Phyllotreta nemorum, the other (P) is susceptible. The two typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…The genetic structure of Muey Nawng appears to be much more influenced by genetic differentiation between gall midge‐resistant and susceptible types. A similar pattern is found in flea beetle‐resistant Barbarea vulgaris populations across Denmark where resistant and susceptible populations are clustered into separate genetic groups (Hauser et al , ). Studies of two Silene species across a large geographical scale showed not only structure due to resistance and susceptibility to anther smut fungus ( Microbotryum ), but also revealed geographical structuring across Europe (Vercken et al , ).…”
Section: Discussionsupporting
confidence: 65%
“…The genetic structure of Muey Nawng appears to be much more influenced by genetic differentiation between gall midge‐resistant and susceptible types. A similar pattern is found in flea beetle‐resistant Barbarea vulgaris populations across Denmark where resistant and susceptible populations are clustered into separate genetic groups (Hauser et al , ). Studies of two Silene species across a large geographical scale showed not only structure due to resistance and susceptibility to anther smut fungus ( Microbotryum ), but also revealed geographical structuring across Europe (Vercken et al , ).…”
Section: Discussionsupporting
confidence: 65%
“…2). However, occasional P-type populations in S. Scandinavia have been described in earlier papers from our research group (Agerbirk et al, 2001;Toneatto et al, 2010; ( Hauser et al, 2012;Christensen et al, 2014), suggesting that the Ptype may occur far into the apparent G-type dominated area at lower frequencies.…”
Section: Ecological Aspects Of Glucosinolate Variationmentioning
confidence: 68%
“…As the deviating P-type bears no clear resemblance to other tested Barbarea species (Agerbirk et al, 2003;Toneatto et al, 2012), the second hypothesis has no experimental support yet. In contrast, the theory of past allopatric separation has been supported by a recent demonstration of different geographic distributions of the two types: based on the characteristic genetic profiles of the P and G-types, the P-type was found to be widely distributed in Eastern Europe in contrast to a more western distribution of the G-type (Christensen et al, 2014;Hauser et al, 2012). Resistance properties and metabolite analysis of most of the accessions generally agreed with the genetic assessment of plant type status based on five unlinked microsatellite markers, but GSL data of two accessions were atypical.…”
Section: Introductionmentioning
confidence: 99%
“…Within the large crucifer family (Brassicaceae), only a few species in the genus Barbarea are known to produce saponins (Badenes-Perez et al, 2014). One of these species, Barbarea vulgaris, has diverged into two different 'plant types' that differ in saponin profile and herbivore resistance, as well as in other defense-related traits Hauser et al, 2012;Toneatto et al, 2012). One type, the G-type (Glabrous), is resistant to some specialist insect herbivores, including the devastating agricultural pest diamondback moth (Plutella xylostella) and the flea beetle (Phyllotreta nemorum).…”
Section: Introductionmentioning
confidence: 99%